Epidemiology and Burden of Human Papillomavirus and Related Diseases, Molecular Pathogenesis, and Vaccine Evaluation - Kombe Kombe, Arnaud John; Li, Bofeng; Zahid, Ayesha; Mengist, Hylemariam Mihiretie; Bounda, Guy-Armel; Zhou, Ying; Jin, Tengchuan (Frontiers in Public Health, 2021)
Diagnosed in more than 90% of cervical cancers, the 4th deadliest cancer in women, human papillomavirus (HPV) is currently the 1st pathogen responsible for female cancers. Moreover, HPV infection is associated with many other diseases including cutaneous and anogenital warts, and genital and upper-aerodigestive tract cancers. Incidence and prevalence of these pathologies vary considerably depending on factors including HPV-genotype, regional conditions, the study population, and the anatomical site sampled. Cervicovaginal microbiota features have been very recently associated with HPV-related disaster incidence as well, making it a novel way to diagnosing high-risk women both through blood and cervix samples. Overall, the HPV repartition data show that HPV infection and related-diseases are more important in developing countries. Moreover, the available (2-, 4- and 9-valent) vaccines based on virus-like-particles, despite their proven effectiveness and safety, present some limitations in terms of system development cost, transport cold chain, and oncogenic-HPVs strains. In addition, the vaccination programs face some challenges, thus, still leading to a considerable burden of HPV-infection and related-diseases. Therefore, even though the new (9-valent) vaccine seems promising, next-generation vaccines, as well as awareness programs associated with HPV-vaccination and, budget reinforcements toward immunization are needed.